A Preliminary investigation of the possible hypoglycaemic activity of Asteracanthus longifolia - Fernando, M.R.; Wickramasinghe, N.; Thabrew, M.I.; Karunanayaka, E.H. (Elsevier, 1989)
Investigations were carried out to confirm or otherwise disprove the view held by many Ayurvedic and other traditional medical practitioners in Sri Lanka, that Asteracanthus longifolia possesses hypoglycaemic properties. The effects of an aqueous extract of the whole plant on fasting blood glucose level and glucose tolerance were investigated using Sprague-Dawley rats. The results indicate that aqueous extracts of A. longifolia can significantly lower the fasting blood glucose level and markedly improve the glucose tolerance of the rats. The hypoglycaemic effect produced by a therapeutic dose (equivalent to 5 g/kg of starting material) was comparable to that produced by a therapeutic dose (15 mg/kg of tolbutamide. The magnitude of the hypoglycaemic effect was found to vary with the dosage administered and the storage time of the prepared extract.
Indexed in MEDLINE
Keywords: Plant Extracts; Plant Extracts-pharmacology; Plants, Medicinal; Hypoglycemic Agents; Tolbutamide-pharmacology